The potential for Ghana to become a leader in the African hemp industry - Richard Quansah Amissah (BMC, 2023)
Abstract Background Global interest in hemp cultivation and utilization is on the rise, presenting both challenges and opportunities for African countries. This article focuses on Ghana's potential to establish a thriving hemp sector, considering its favorable climate, abundant agricultural resources, and existing policies and programs that support the growth and advancement of the agricultural sector, as well as agro-processing and value addition. Main body Ghana's recent decriminalization of cannabis with low tetrahydrocannabinol (THC) levels marks a progressive step, unlocking opportunities for research, commercial production, and innovation in hemp-related sectors. This regulatory change paves the way for the development of textiles, construction materials, and wellness products derived from hemp. However, the African hemp industry faces various simultaneous challenges, including pest management, absence of regulatory frameworks, limited research, inadequate infrastructure, and lack of access to finance and investment capital for small-scale farmers. Fortunately, several countries that have legalized hemp cultivation and processing have found innovative solutions to these challenges through the use of integrated pest management strategies, establishing collaborations with international standards organizations, implementing public-private partnerships, offering tax incentives for investors, and providing low-interest loans and credit facilities for small-scale farmers. Ghana can draw inspiration from these successful approaches and adapt them to its own context to foster the growth of the hemp industry. Conclusion By capitalizing on its strengths and addressing the challenges it is likely to face while developing its hemp industry, Ghana can position itself as a leader in the African hemp industry. This position of leadership would not only drive economic growth, but also create job opportunities and foster sustainable development through responsible hemp cultivation and utilization.